Geography of stock markets. - Wójcik, D (Blackwell Publishing, 2009)
Geography matters for stock markets. Stock market actors and institutions do not just have to be somewhere, but where they are in relation to other actors and institutions has an effect on their behaviour and performance. Hence, the geography of stock markets is crucial to the spatial distribution of financial services and centres. On another level, the evolution and structure of stock markets involves a complex interplay of politics, technology, economy and culture, and can never be explained with economic models alone. Finally, stock markets do not just reflect economy and society, they influence how economy and society work. The current financial crisis only underscores the value of geography as a lens through which to view stock markets, and the significance of the latter in the world economy.